LIFE AND WORK OF PEOPLE IN THE VILLAGE OF MARENOVO - Zdravković, Vladimir; Jelić, Sreten; Vučković, Dejana (ACADEMIC REVIEW, 2022)
This work points out the most significant determinants of the village of Marenovo, which belongs to the municipality of Varvarin. The subject of this work is the research of traditional and contemporary events in the village of Marenovo. The aim of the work is to investigate the development of the village, the culture of the people in the village, get acquainted with the traditions and customs, determine the mentality of the people and understand what the future of the inhabitants of this village is. Several scientific methods were used in the work: the method of description, with tabular and graphical presentation of the described phenomena, the survey method, the interview method and the induction method. Thirty households participated in the survey, in the period from 6.3.2022. until 31.3.2022. The obtained data were processed and analyzed in the IBM SPSS Statistics program. Based on the research conducted, the following was established: the inhabitants of this village have normal living conditions, the relationship with the neighbors in the village is very important, there are no sociopathological phenomena in the village and moral values and traditions have been preserved in the village. The problem that the village of Marenovo is facing is the depopulation due to the migration of locals to the city and abroad.